The impact of formulation change and R&D cooperation types on the eWOM of extension products. Issue 9 (20th May 2020) - Kim, Nayeong; Hwang, Jihee; Lee, Dongmin; Jeong, Jaeseok; Moon, Junghoon
Abstract : Purpose: The purpose of this paper is to investigate the effect of formulation categories (parent brand and extension product) and research and development (R&D) cooperation types on electronic word-of-mouth (eWOM) volume for extension products. Design/methodology/approach: This study uses data from 109 extension products in the Korean dessert market whose formulations were changed between 1 February 2014 and 19 February 2019. The formulation categories and R&D cooperation types are transformed into dummy variables to conduct a linear regression. Findings: The formulation categories and R&D cooperation types play key roles in proliferating eWOM for formulation change products. The most effective way to proliferate eWOM is through product extension by changing the formulation of ice cream, beverage and snack category products. Furthermore, vertical R&D cooperation positively affects the proliferation of products' eWOM. Originality/value: These findings contribute to increasing the chance of successful food product development by providing information on the formulation changes that are effective at inducing consumers' interest.